PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Asran; Wa Ode Rayyani; Abdul Khaliq (STKIP Subang, 2026)
This study aims to determine the effect of Corporate Social Responsibility (CSR) disclosure on financial sector performance in healthcare manufacturing companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The research method used was quantitative. The sample was selected using a purposive sampling technique, resulting in five companies meeting the research criteria, with a total of 25 observational data sets. The data used were secondary data obtained from annual reports and sustainability reports. The analytical technique used in this study was simple linear regression analysis using SPSS version 25. The results showed that Corporate Social Responsibility (CSR) coverage did not significantly affect Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). This indicates that corporate CSR disclosures have not yet had a direct impact on improving financial performance. CSR tends to be viewed as a form of corporate social responsibility and obligation to society and the environment, so its impact on corporate profitability has not been significantly seen in the short term.